Pharmacokinetics and allometric analysis of spectinomycin - T. Dinev (Trakia Journal of Sciences)
In this study were compared microbiological and HPLC methods for determination of spectinomycin pharmacokinetics in goats. The goats were subject to intravenous administration of spectinomycin at 20 mg/kg body weight. For the microbiological assay was used test microorganism Sarcina lutea ATCC 9341. Limit of quantification in the microbiological assay was 6.25 μg/mL and in the HPLC method was 0.1 μg/mL. Spectinomycin concentrations following microbiological assay were initially higher than HPLC-determined and gradually the differences decreased. During HPLC analysis spectinomycin was found until 12 h and during microbiological assay until 4 h. As a result in HPLC analysis the values of Vd(area) (0.527 L/kg) , t1/2β (1.74 h) and ClB (3.512 mL/kg/min) were considerably higher in comparison with microbiological method (Vd(area) - 0.147 L/kg , t1/2β - 0.8 h and ClB - 2.174 mL/kg/min). The data from method validation also showed the advantage of HPLC method. Because of that can be concluded that HPLC is more sensitive and accurate method for spectinomycin determination. Regarding the allometric equation for elimination half-life (t1/2 = 1.19.W0.02) the values are showing lack of correlation to body weight. Volume of distribution allometric equation (Vd(area) = 0.37.W0.96) and total body clearance allometric equation (ClB = 1.92.W1.09) have high level of correlation to body weight (<0.001) and therefore can be used.